Cadaveric Simulation Training in Cardiothoracic Surgery: A Systematic Review. Issue 3 (10th July 2019) - Robinson, Davida A.; Piekut, Diane T.; Hasman, Linda; Knight, Peter A.
Abstract : Simulation training has become increasingly relevant in the educational curriculum of surgical trainees. The types of simulation models used, goals of simulation training, and an objective assessment of its utility and effectiveness are highly variable. The role and effectiveness of cadaveric simulation in cardiothoracic surgical training has not been well established. The objective of this study was to evaluate the current medical literature available on the utility and the effectiveness of cadaveric simulation in cardiothoracic surgical residency training. A literature search was performed using PubMed, Cochrane Library, Embase, Scopus, and CINAHL from inception to February 2019. Of the 362 citations obtained, 23 articles were identified and retrieved for full review, yielding ten eligible articles that were included for analysis. One additional study was identified and included in the analysis. Extraction of data from the selected articles was performed using predetermined data fields, including study design, study participants, simulation task, performance metrics, and costs. Most of these studies were only descriptive of a cadaveric or perfused cadaveric simulation model that could be used to augment clinical operative training in cardiothoracic surgery. There is a paucity of evidence in the literature that specifically evaluates the utility and the efficacy of cadavers in cardiothoracic surgery training. Of the few studies that have been published in the literature, cadaveric simulation does seem to have a role in cardiothoracic surgery training beyond simply learning basic skills. Additional research in this area is needed.